2016
DOI: 10.1007/s10709-016-9903-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrative taxonomy supports new candidate fish species in a poorly studied neotropical region: the Jequitinhonha River Basin

Abstract: Molecular identification through DNA barcoding has been proposed as a way to standardize a global biodiversity identification system using a partial sequence of the mitochondrial COI gene. We applied an integrative approach using DNA barcoding and traditional morphology-based bioassessment to identify fish from a neotropical region possessing low taxonomic knowledge: the Jequitinhonha River Basin (Southeastern Brazil). The Jequitinhonha River Basin (JRB) has a high rate of endemism and is considered an area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 51 publications
3
26
0
1
Order By: Relevance
“…In addition, no other neoplecostomine have been reported in that basin since Oliveira, Oyakawa (1999) described Pareiorhaphis stephanus from the ribeirão das Pedras, a headwater tributary to the rio Jequitinhonha basin near Diamantina, 2 e170007 [2] Minas Gerais State. Recently, however, a possible second species of Pareiorhaphis has been identified based on DNA barcode comparison and since its genetic distance from P. stephanus was higher than 2% (namely 5.79%), it was considered a candidate new species by Pugedo et al (2016), what was confirmed with the present morphometric analysis. Various ichthyological surveys conducted by the authors in tributaries to upper and middle portions of the rio Jequitinhonha basin during the last few years, have produced good series of that distinct, undescribed species of Pareiorhaphis, which is formally described in the present paper.…”
Section: Introductionsupporting
confidence: 82%
“…In addition, no other neoplecostomine have been reported in that basin since Oliveira, Oyakawa (1999) described Pareiorhaphis stephanus from the ribeirão das Pedras, a headwater tributary to the rio Jequitinhonha basin near Diamantina, 2 e170007 [2] Minas Gerais State. Recently, however, a possible second species of Pareiorhaphis has been identified based on DNA barcode comparison and since its genetic distance from P. stephanus was higher than 2% (namely 5.79%), it was considered a candidate new species by Pugedo et al (2016), what was confirmed with the present morphometric analysis. Various ichthyological surveys conducted by the authors in tributaries to upper and middle portions of the rio Jequitinhonha basin during the last few years, have produced good series of that distinct, undescribed species of Pareiorhaphis, which is formally described in the present paper.…”
Section: Introductionsupporting
confidence: 82%
“…Though the sample sizes are too low to be conclusive on their own, this level of differentiation suggests the presence of at least three distinct species under a phylogenetic species concept. Similar levels of differentiation have been found among other closely related species in Leporinus (Avelino et al, 2015), as well as many other Neotropical fish groups (Gomes et al, 2015;Pugedo et al, 2016).…”
Section: Tabsupporting
confidence: 77%
“…The goal of this campaign is to allow fish species identification through the comparison of query sequences against the reference sequence database in the Barcode of Life Data Systems, BOLD (Ratnasingham & Hebert, 2007). DNA barcode libraries also facilitate species discovery when morphology alone is insufficient (April, Mayden, Hanner, & Bernatchez, 2011) and particularly in poorly inventoried areas characterized by taxonomically hyperdiverse faunae (Pereira, Hanner, Foresti, & Oliveira, 2013;Pugedo, Andrade Neto, Pessali, Birindelli, & Carvalho, 2016).…”
Section: Introductionmentioning
confidence: 99%